(untitled) (University of Khartoum Engineering Journal, 2021)
This paper presents and discusses the experience gained through the application of base grouting technique applied for improving the capacity of large diameter bored piles foundation system for two heavily loaded bridge structures. Many large diameter bored piles were installed in Sinnar bridges project, Sudan and base treated by cement grout pumped at high pressures to preload the soil beneath their tips. The post construction operation was conveniently implemented for 106 bored piles of 1.5 to 2.0m diameter and 42 to 50m long utilizing equipments that are not sophisticated or expensive. The successful application of base grouting provided valuable insight into the technique’s merits over the currently practiced construction techniques such that the pile’s base capacity component is realized within service displacement limits. The study results indicate that base grouting can substantially improve the ultimate capacities by 2.15 to 2.62 times the values usually estimated for ungrouted bored piles of the same dimensions installed in similar soil conditions. From a foundation design viewpoint, safety factors much lower than those often used for ungrouted bored piles can be adopted for grouted piles of the same dimensions installed at a given site. Otherwise, the dimensions of grouted piles can be reduced whilst providing equivalent capacities as those of ungrouted piles with larger sizes. This will lead to a cost effective foundation design, improve the construction methodology and eventually enhance the overall performance of bored piles foundation when used in future projects.